Papel atual dos métodos de imagem no diagnóstico das neoplasias císticas e sólidas do pâncreas: 1ª parte - Ardengh, José Celso (2011)
The authors address the value of endoscopic retrograde cholangiopancreatography, ultrasonography, computed tomography, magnetic resonance imaging and endoscopic ultrasound for the diagnosis of cystic and solid neoplasms of the pancreas, demonstrating that each of them is of great importance to undoubtedly increase the diagnostic accuracy of the biliopancreatic system diseases. The best method for each of several tumors is then determined.